Which of the following equations represents the inverse of y = e2x - 9?
![Which of the following equations represents the inverse of y e2x 9 class=](https://us-static.z-dn.net/files/d6f/c696ef9db8541f9c730fa840f22d13de.gif)
![Which of the following equations represents the inverse of y e2x 9 class=](https://us-static.z-dn.net/files/dc6/577c3205db5966e2fc518f69f8ffabdd.gif)
![Which of the following equations represents the inverse of y e2x 9 class=](https://us-static.z-dn.net/files/d59/5875cf91f5565999aa17bdc1895b1fca.gif)
![Which of the following equations represents the inverse of y e2x 9 class=](https://us-static.z-dn.net/files/d04/94e056ff4272444e4e0be3952b105588.gif)
Answer:
[tex]y=\frac{1}{2} \ln(x+9)[/tex]
Step-by-step explanation:
The given function is
[tex]y=e^{2x}-9[/tex]
Interchange x and y.
[tex]x=e^{2y}-9[/tex]
Solve for y.
[tex]x+9=e^{2y}[/tex]
Take logarithm of both sides to base e.
[tex]\ln(x+9)=2y[/tex]
Divide both sides by 2.
[tex]y=\frac{1}{2} \ln(x+9)[/tex]
Answer:
[tex]\frac{1}{2}ln(x+9) = y[/tex]
Step-by-step explanation:
We have given an equation.
[tex]y = e^{2x} -9[/tex]
We have to find the inverse of the equation.
Adding 9 to both sides of above equation, we have
[tex]y+9 = e^{2x} +9-9[/tex]
[tex]y+9 = e^{2x}[/tex]
Taking logarithms to both sides of above equation, we have
[tex]ln(y+9) = ln(e^{2x})[/tex]
[tex]ln(y+9) = 2x[/tex]
Dividing by 2 to both sides of above equation, we have
[tex]\frac{1}{2}ln(y+9) = x[/tex]
Putting x = f⁻¹(y) in above equation ,we have
[tex]\frac{1}{2} ln(y+9) = f^{-1}(y)[/tex]
Replacing y by x , we have
[tex]\frac{1}{2}ln(x+9) = f^{-1}(x)[/tex]
[tex]\frac{1}{2}ln(x+9) = y[/tex] which is the answer.